Managing Chinese Baby Formula Milk Powder Competitiveness from Operations Management: An Action Research on Junlebao Dairy Co., Ltd - Dong, Bo (2014)
In the past decades, China has undergone tremendous change. It has been one of the fastest growing economies around the world. The high speed growth of GDP highly increased the customers’ purchasing power in the market, which also brought huge development opportunities to the enterprises. Especially after 2000, small and medium enterprises rose abruptly, and made great contribution to China’s economic achievement. But that also induced over-enthusiastic business expansion. Substantial amount small and medium enterprises were more eagerly to be ‘larger’ but neglected to be ‘stronger’. Under the graceful short-term market-side performance achievements, a lot of operation issues were corroding the business. From a long-term view, the unilateral development is rather dangerous to cause significant problems which may ruin an enterprise’s destiny and influence the entire industry and whole market. Operation to an enterprise just like the root system to a tree, sufficient provisions victuals is the support of the growth and health. Based on the lessons drawn from predecessors' mistakes, milk powder producers should be established in operations management development, enhance quality management and innovate distribution network to add more value to customers. So that to eliminate confidence crisis and reduce the price. Hence, promote customer satisfaction. The dissertation was supported by an eight-week action research of Junlebao Dairy co., Ltd. Moreover the deputy secretary general of Hebei Society of Quality and Brand was interviewed in order to obtain the information about government’s influence to baby formula milk powder producers’ operations management. Through the action research, the key factors that are for and against the development of the industry and improvement of operations management were analysed. Order winners and order qualifiers and the competitive criteria gaps to the case company were discussed. SCOR model was applied to analyse the case company’s milk powder supply chain. Government behaviours’ impacts to enterprises’ supply chain were indicated particularly. The barriers restricted the company’s competitiveness were concluded as its unilateral quality management and simplex distribution. The implementations of TQM and O2O e-commerce model were carried out to offset the company’s shortages in operations. Meanwhile, the research faced several limitations. Firstly, the single sample weakened the generality of the findings. Secondly, due to the protection of the business secret, the quality data and product design process were not exposed to the researcher. Thirdly, the observing and reflecting process of the action research were not completed due to time limitation. Fourthly, the direct contact to related government sectors was not accessed which considerably influenced the depth of government impactions analysis. These limitations should be compensated in the future research.